GERMINATION OF Piptadenia moniliformis Benth SEEDS UNDER WATER STRESS - Azeredo, Gilvaneide Alves de; Paula, Rinaldo Cesar de [UNESP]; Valeri, Sergio Valiengo [UNESP] (Centro Pesquisas Florestais, Ufsm, 2016)
The period of germination and the establishment of seedlings are important factors for the survival of species, mainly in places where availability of water is limited, as in the Caatinga region. In this sense, the purpose of this research was to evaluate the effect of water stress on the germination of Piptadenia moniliformis Benth seeds. Three lots (L-1, L-2 e L-3) were used, corresponding to the production years of 2006, 2007 and 2008, respectively. Before the germination test, the seeds were submitted to scarification in concentrated sulfur acid for 30 minutes. To induce water deficit, polyethyleneglicol (PEG 6000) was used, in the following osmotic potentials: - 0,3; -0,6; -0,9, -1,2 and -1,5 MPa and water (0 MPa) under the temperatures of 25 and 30 degrees C. The features the experiment evaluated were: percentage of germination and of normal seedlings, germination speed index and the dry mass of seedlings. The germinating process of Piptadenia moniliformis Benth seeds is jeopardized from water potentials inferior to -0,6 MPa at 25 and 30 degrees C; water potentials equivalent or inferior to -1,2 MPa inhibit the formation of normal seedlings in both temperatures; the tolerance to water stress simulated with PEG 6000 is variable among seedling lots and germination temperatures.
Keywords: PEG; seedlings growth; Caatinga